(untitled) (Sound Stage Screen, 2023)
Edited by Giorgio Biancorosso and Emilio Sala. Contributions by Gillian Anderson, Steven Feld, Michal Grover-Friedlander, Yuichi Kinoshita, Rina Tanaka, Yao Chen, and Judith Zeitlin.